Student Entrepreneurship, Prospect or Problems? (Identifikas Jenis dan Permasalahan Yang Dihadapi Mahasiswa Fakultas Ekonomi Universitas Katolik Parahyangan Dalam Memulai dan Menjalankan Bisnis) - Fernando Fernando; Vincentia Wahyu (Research Report - Humanities and Social Science, 2015)
People without any college education who start a business have a greater chance of failing than people with one or more years of college education (Lussier & Halabi, 2008). Lussier & Halabi research at Chile concludethat study experience at higher education institution is significant for their success when they starting up business.Parahyangan Catholic University (also known as UNPAR) is one the oldest private university in Indonesia.UNPAR established in 1955, and its first Faculty is Economics. Many of its Economics Faculty alumni even its students became entrepreneur, but did study at Economics faculty help them when they started up their business?This research purposes is to identify kind of business owned by students of Parahyangan Catholic University Faculty of Economics, identify problems when they started they own business and identify problems when theyrunning the business.The Research method used in this research is descriptive Study. Descriptive Study is undertaken in order to ascertain and be able to describe the characteristic of the variables of interest in a situation (Sekaran and Bougie, 2010). More specific interview is used to gather data from students who already started their business during their study.Keyword:Entrepreneurship, Entrepreneur, Student Entrepreneurship, Entrepreneurial Competencies